Characteristics of patients with Hepatitis B and C at Dr. Moewardi General Hospital in Surakarta, Indonesia - Benedictus Aditya Satya Laksana Adji; Triyanta Yuli Pramana; Tri Nugraha Susilawati (Universitas Gadjah Mada, 2022)
Hepatitis B virus (HBV) and hepatitis C virus (HCV) infections remain a significant health burden in the world, which is mainly attributed to patients who develop chronic hepatitis, liver cirrhosis, and hepatocellular carcinoma (HCC). The epidemiology of hepatitis B and C in Surakarta, Central Java Province, Indonesia has never been reported. This study aimed to investigate the demographic, clinical, and laboratory characteristics of patients with hepatitis B and C who were admitted to Dr. Moewardi General Hospital, Surakarta in 2019. The medical records of patients with hepatitis B (n=94) and hepatitis C (n=75) were examined, and the data were analyzed using the chi-square and Mann-Whitney tests. The patients with hepatitis C were generally older, more likely to develop jaundice and ascites, and had higher levels of serum urea, creatinine, AST, and total bilirubin compared to those with hepatitis B. In conclusion, patients with HCV infection had worse clinical presentation and laboratory profiles than those with HBV infection. However, further research is needed on a wider scale to confirm this result.